Journalism and Fact-Checking Technologies: Understanding User Needs - Laurence Dierickx (communication +1, 2023)
Fact-checking, defined as verifying information before publication, has become a prominent sub-genre of journalism over the last decade. These activities are characterized by their time-consuming aspects at each step of the process. However, it would be misleading to view this process as a sum of repetitive tasks insofar as they also depend on the nature, either textual or visual, and on the complexity of the domain related to the fact to check. Fact-checking tools are a part of the fact-checker apparatus. In this research, we provide evidence on the condition of the use of fact-checking tools, mobilizing a theoretical framework that explores the epistemology of the use and user experience concepts. This interdisciplinary approach grounded a method that relied on semi-structured interviews with fourteen professional fact-checkers and three newsroom managers from well-established news media or fact-checking organizations in Northern and Western Europe. It allowed us to identify common patterns where ethical standards of journalism and fact-checking come to the fore. The two other main requirements are a transparent and explainable process and keeping the human in the loop. Still, the use of fact-checking tools fits more into a utilitarian approach, according to which technology is not an end but a means likely to assist or augment professional practices.Note: Download statistics restarted from zero effective January 1, 2024. Please follow this link to see cumulative download statistics from our previous publishing platform: CPO Download Statistics 2012 - 2023